Photosynthesis, yield, energy balance, and water‐use of intercropped maize and soybean. (14th December 2021) - Pelech, Elena A.; Alexander, Brendan C. S.; Bernacchi, Carl J.
Abstract: By 2050, the U.S. Corn Belt will likely face a 23% increase in leaf‐to‐air vapor pressure deficit (VPDL ), the driving force of evapotranspiration (ET), which may restrict maize yield improvements for rainfed agroecosystems. Alternative cropping systems, such as maize and legume intercrops, have previously demonstrated yield and resource‐use advantages over monocultures. In this study, the residual energy balance approach was used to gain insights into how an additive simultaneous maize and soybean intercrop system regulates ET and water‐use efficiency (WUE) compared to standard maize and soybean monoculture systems of the U.S. Corn Belt. Experimental field plots were rain‐fed and arranged in a randomized complete block design in three blocks. Photosynthetic capacity and grain yield of maize were conserved in the intercrop. However, its competitive dominance shaded 80%–90% of incident light for intercropped soybean at canopy closure, leading to a 94% decrease in grain yield compared to soybean monoculture. The total grain yield per unit area of the additive intercrop (land‐use efficiency) increased by 11% ± 6% (1 SE). Compared to maize monoculture, the intercrop had higher latent heat fluxes ( λ ET) at night but lower daytime λ ET as the intercrop canopy surface temperature was approximately .25°C warmer, partitioning more energy to sensible heat flux. However, the diel differences in λ ET fluxes were not sufficient to establish a statistically significant or biologically relevant decrease in seasonal water‐use (ΣET). Likewise, the increase in land‐use efficiency by the intercrop was not sufficient to establish an increase in seasonal water‐use efficiency. Intercropping high‐performing maize and soybean cultivars in a dense configuration without negative impact suggests that efforts to increase yield and WUE may lead to improved benefits.